Ethnoveterinary studies of medicinal plants used to treat livestock in the Haridwar region of Uttarakhand, India - Sharma, Munish; Bithel, Navneet; Sharma, Munit (Current Botany, 2022)
Ethnoveterinary practices are still prevalent in rural livestock healthcare. This research contributes significantly to the understanding of biological resources employed in ethnoveterinary practices in the Haridwar district of Uttarakhand. This current study focuses on ethnoveterinary knowledge among ethnic populations in Haridwar and quantitatively documented the traditional knowledge about the usage of different medicinal herbs. The field survey was carried out at four sampling sites, i.e., Chilla range, Mohand range, Vindhyavasini hills, and Shyampur range. The ethnoveterinary information was documented and collected in the study areas through interviews, questionnaires, and group discussions with ethnic communities and traditional healers, primarily elderly shepherds and farmers. The collected data were quantitatively analysed utilizing the informant consensus factor (ICF), fidelity level (FL), and use value (UV). In this study, 102 medicinal plant species were identified in which herbs (58.8%) were the maximum used life forms. Leaves (27.1%) were found to be the most commonly used plant part. The oral mode of medication was used most often in the ethnoveterinary practices (79.4%) used. Quantitative analysis revealed that the most important species having high UV values for curing livestock was Zingiber officinale (L) (UV = 2.67). FL% values ranged between 27.8 to 100% and ICF values ranged from 0.97 to 0.99. This study reveals that a large variety of medicinal plant species are of great ethnoveterinary relevance and are used by informants in Haridwar to treat cattle ailments. Further phytochemical and pharmacological studies would be needed to determine the usefulness and safety of the identified plants, allowing communities to use them in a more cost-effective, and safe manner.